Organizational Climate and its Impact in a Women’s Prison on the Mental Health of Correctional Staff - Kim, Joseph (Journal of contemporary criminal justice, 2024)
The purpose of this study was to explore the organizational climate in a women’s prison from the shared perceptions of correctional staff. This study was part of the Prison Research and Innovation Network (PRIN) project, which began in the fall of 2020. Forty-two correctional staff from a low-medium security women’s prison in the Midwest were interviewed in spring 2021. Thematic analysis was conducted to identify staff’s perceptions of organizational climate in the women’s correctional facility. The themes identified as most important to staff were mental health, correctional practices, job satisfaction, and workplace culture. An item pool was developed from the themes identified, and a newly developed organizational climate survey was administered to 80 correctional staff. Qualitative data point to the issues of staff shortages and mandated overtime work impacting the mental health of staff. In addition, organizational climate and its impact on mental health were examined through multiple logistic regressions. The results indicated that having job promotion opportunities, having daily communication between staff and administration, and staff’s knowledge and awareness of correctional policies were positively associated with mental health. This mixed-methods study contributes to understanding the unique challenges correctional staff face working in women’s correctional facilities.